A modeling dialog with AI – what do we learn about what we have to learn? - Joolingen, Wouter van (2024)
Generative AI (GenAI) is a relatively new phenomenon with already an enormous impact. Many tasks, from searching for information to computer coding have fundamentally changed. For instance, creating computer code is a task that a chatbot like ChatGPT can do for many programming problems. This might move the focus of programming away from the code itself to the more conceptual aspects of the task. In this paper we will explore the consequences for science education, in particular for scientific modeling.